Navigating reality: exploring points of interest with augmented reality - Muhammad Kharibi, Nadiah; Toha, Siti Fauziah; Azmi, Nur Liyana; Idris, Ahmad Syahrin; Tokhi, M. Osman (Persatuan Saintis Muslim Malaysia (PERINTIS), 2024)
The implementation of augmented reality (AR) has significantly enhanced productivity by delivering real-time information and data, enabling users to stay infonned about their surroundings. In recent years, AR adoption has grown rapidly across various industries, including agriculture, which has increasingly embraced tourism. While tourists often face an overwhelming amount of information available online, this challenge can be addressed with innovative solutions. With smartphones serving as the primary platform for AR, the development of supporting software has seen explosive growth. Tourism, as a vital and evolving economic sector, continually adopts advanced technologies to attract younger, adventurous travelers. AR holds great promise for enhancing the travel experience, offering features like real-time translation, mapping, and travel guidance. To leverage this potential, the mobile application Malay AR was developed to provide personalized Point of Interest (POI) recommendations based on user preferences and location. The app incorporates a user profile page and AR-powered POI detection for engaging navigation. Initial findings reveal an average deviation of 8.49 meters across five landmarks, but AR integration significantly mitigates this deviation, ensuring precise location guidance and improved urban navigation and tourist engagement.